UPAYA PENINGKATAN KETERAMPILAN MENYIMAK DALAM PEMBELAJARAN BAHASA INDONESIA MELALUI PEMANFAATAN MEDIA AUDIO-VISUAL BAGI PESERTA DIDIK SEKOLAH DASAR - Siti Nur Afiyatus Salamah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research focuses on efforts to enhance students' listening skills in Indonesian language learning, specifically on the prefix "ber-", through the utilization of audio-visual media in the teaching and learning process for fourth-grade students at UPT SD Negeri Baturetno 1 Tuban. The method employed in this study is Classroom Action Research (CAR), conducted directly in the classroom. The research targets 16 students, both male and female. The implementation of the study is carried out in two cycles, which include the stages of planning, action, observation, and reflection. Listening ability tests are used as data collection methods in both cycles, along with documentation. The findings indicate that students' listening skills have improved, rising from 52.8% at the pre-action stage to 71,37% in Cycle I, and experiencing a significant increase to 82.3% in Cycle II. Additionally, students' enthusiasm and active participation in the teaching and learning activities also showed improvement. These results suggest that the integration of audio-visual media during the Indonesian language learning process on the prefix "ber-" is effective in enhancing the listening skills of fourth-grade students at UPT SD Negeri Baturetno 1 Tuban.